Геоурбанистика: учебное пособие - Соболева Н. П. Надежда Петровна; Замятина Ю. Л. Юлия Леонидовна; Барановская Н. В. Наталья Владимировна; Жорняк Л. В. Лина Владимировна (Томск, Изд-во ТПУ, 2012)
Заглавие с титульного экрана